Anticoagulants for secondary prevention after acute myocardial infarction: lessons from the past decade. (10th March 2014) - Atar, Dan; Bode, Christoph; Stuerzenbecher, André; Verheugt, Freek W. A.
Abstract The impact of an acute coronary syndrome (ACS) event, such as an acute myocardial infarction (MI), is not limited to the acute management phase; patients face an elevated risk of residual atherothrombotic events that commonly requires chronic management for months or even years. Significant advances have been made in both the acute and chronic management of patients with acute MI over the past decade, resulting in improved prognoses. One of the hallmarks of modern treatment strategies is more aggressive antiplatelet treatment regimens. However, the risks of further ACS events, stroke and premature death remain elevated in these patients, and addressing this residual risk is challenging owing to interpatient variability, differences in management strategies between centres and countries, incomplete understanding of the specific pathophysiology of post‐ACS thrombosis and limitations of current therapeutic approaches. The recent approval in Europe of the direct oral anticoagulant rivaroxaban for use in this setting in combination with clopidogrel and acetylsalicylic acid offers another strategy to consider in the management of these patients, and clinical strategies in this area continue to evolve. In this review, we chart the progress made over the past decade in reducing the burden of secondary thromboembolic events after acute MI and discuss the current position of and future perspectives on the inclusion of oral anticoagulants into care pathways in this setting.